Engineered α4β2 nicotinic acetylcholine receptors as models for measuring agonist binding and effect at the orthosteric low-affinity α4–α4 interface. (May 2015) - Ahring, Philip K.; Olsen, Jeppe A.; Nielsen, Elsebet Ø.; Peters, Dan; Pedersen, Martin H.F.; Rohde, Line A.; Kastrup, Jette S.; Shahsavar, Azadeh; Indurthi, Dinesh C.; Chebib, Mary; Gajhede, Michael; Balle, Thomas
Abstract: The nicotinic acetylcholine receptor α4β2 is important for normal mammalian brain function and is known to express in two different stoichiometries, (α4)2 (β2)3 and (α4)3 (β2)2 . While these are similar in many aspects, the (α4)3 (β2)2 stoichiometry differs by harboring a third orthosteric acetylcholine binding site located at the α4–α4 interface. Interestingly, the third binding site has, so far, only been documented using electrophysiological assays, actual binding affinities of nicotinic receptor ligands to this site are not known. The present study was therefore aimed at determining binding affinities of nicotinic ligands to the α4–α4 interface. Given that epibatidine shows large functional potency differences at α4–β2 vs . α4–α4 interfaces, biphasic binding properties would be expected at (α4)3 (β2)2 receptors. However, standard saturation binding experiments with [ 3 H]epibatidine did not reveal biphasic binding under the conditions utilized. Therefore, an engineered β2 construct (β2 HQT ), which converts the β(−) face to resemble that of an α4(−) face, was utilized to create (α4)3 (β2 HQT )2 receptors harboring three α4–α4 interfaces. With this receptor, low affinity binding of epibatidine with a Kd of ∼5 nM was observed in sharp contrast to a Kd value of ∼10 pM observed for wild-type receptors. A strong correlation between binding affinities at the (α4)3 (β2 HQT )2 receptor and functional potencies at the wild-type receptor of a range of nicotinic ligands highlighted the validity of using the mutational approach. Finally, large differences in activities at α4–β2 vs . α4–α4 interfaces were observed for structurally related agonists underscoring the need for establishing all binding parameters of compounds at α4β2 receptors. Highlights: A radioligand binding assay for the α4–α4 interface of α4β2 nAChRs was established. Agonist affinities and functional potencies at the α4–α4 interface correlate. Understanding agonist activities require both α4–α4 and α4–β2 binding insights. Radioligand binding at wild-type α4β2 nAChRs only reflects binding to α4–β2 interfaces.